Snapshots of Physical Activity: Understanding Primary School Pupils’ Physical Activity Needs (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Integrating short bouts of physical activity into the primary school day to interrupt sedentary learning time can significantly enhance children’s wellbeing. However, many Dutch schools have yet to successfully implement such a more ‘dynamic’ school day. This project aims to inspire and support primary schools in creating a more dynamic school environment tailored to their local context. To achieve this, we sought to understand pupils’ perceptions of physical activity during the school day through photo elicitation sessions.Methods: We organised photo elicitation sessions with pupils aged 8–9 years in six schools. Within each school, two sessions were planned. During the first session, pupils would be divided into small subgroups (3–6 pupils) and each group would guide the researchers through the school. During the guided tour, pupils would make polaroid pictures of the places where they were physically active or inactive. In the second session, pupils reviewed the photos and drew activities they wished to engage in within three settings: the classroom, inside the school, and the schoolyard. The photos and drawings were analysed thematically using the Youth Physical Activity Promotion Model (YPAPM).Results: The results provided us with a better understanding of the perspectives of pupils on the physical activity opportunities and barriers within and around the school. This includes perspectives on the environment (places where pupils are more/less physically active), social interactions (with peers and/or school staff), and emotional influences when pupils participate in physical activity “I like having an active break from work – it helps me concentrate better afterwards”.Conclusion: Our results can help participating schools to make their local plans for a dynamic school day more effective, engaging, and context-specific. Not only can the teachers understand their pupils better, but pupils are also encouraged to come up with child-led solutions, potentially empowering them to take ownership of their own physical activity participation.Support/Funding Source: This study is supported by a RAAK PRO grant from SIA NWO, the Dutch Research Council (Project Number RAAK.PRO05.048).